Pre‑sowing seed treatment with proline, glycine betaine, and soil amendment with compost as strategies for improving yield and drought tolerance in cowpea (2022)
Purpose Drought is one of the major abiotic stresses limiting crop production. Compatible solutes, like proline (P) and glycine betaine (GB) enhance crop tolerance to abiotic stresses. Compost also supplies nutrients to crop and enhances crop tolerance to stress. The effects of pre-sowing seed treatments with P and GB as well as soil amendment with compost on cowpea performance under water deficit stress were investigated in this study. Methodology Cowpea seeds were soaked in P and GB at 0 (distilled water: control), 2.5, 5, and 10 mM for 12 h before sowing. Compost (C) was applied at 2.5, 5, and 7.5 t ha− 1. Water stress was imposed by withdrawing water for 10 (W1) or 20 (W2) days, at vegetative (VS) or reproductive (RS) stages. Data were collected on cowpea growth parameters, yield, nodulation, P, and GB accumulation. Results The W2 at VS reduced cowpea growth and yield by 100% compared to the unstressed plants, while, W1was more tolerable. Proline, GB and C enhanced tolerance, growth, and pod yield, especially with C5 t ha −1, C7.5 t ha −1, GB5mM, and P2.5 mM. Water stress increased P and GB in untreated plants more than the treated plants. Compost at every rate, reduced the accumulation of proline and GB in cowpea under stress (W1), whereas proline was more in plants pre-treated with GB10mM and P2.5 mM under W2 at VS compared to RS. At RS, compost increased P and GB accumulation and these were reduced in P treatments. Conclusion Compost and seed treatment with solutes enhanced cowpea stress tolerance and improved yield.